Professional Commitment And Whistleblowing Intention: The Role Of National Culture - Ni Wayan Rustiarini; Anik Yuesti; Ni Putu Shinta Dewi (Universitas Muhammadiyah Malang, 2021)
This study aims to identify the effect of professional commitment on whistleblowing intentions. This study also analyzes the role of Hofstede's five dimensions of national culture as moderating variable, including power distance, collectivism, masculinity, uncertainty avoidance, and long-term orientation. This study used a survey method. The primary data collection was through a questionnaire distributed to 92 auditors in accounting firms in Bali Province. The result shows that professional commitment positively affects whistleblowing intention. The moderating variable's roles are power distance and collectivism's culture weaken professional commitment and whistleblowing intention relationship. Two other cultures, namely masculinity and a long-term orientation, are proven to strengthen the relationship between professional commitment and whistleblowing intention. Contrary, uncertainty avoidance culture has no significant effect. Theoretically, this study confirms the role of the national culture in the auditing context. This result practically adds insight to regulators and accounting firm leaders in formulating regulations regarding the appropriate whistleblowing system for organizations. There are two limitations. First, this study uses a survey method. This method allows for social desirability bias for sensitive variables, such as whistleblowing. This study also uses the national culture popularized by Hofstede about forty years ago. Thus, further research might use other popular models.